Prevalence and risk factors of anaemia among pregnant women in eastern Nepal - Sinha, Amar Kumar; Singh Karki, Gyanendra Man; Karna, Keshab Kumar; Gaire, Chandra Prakash (Journal of Chitwan Medical College, 2018)
Anaemia is the commonest problem in pregnancy throughout the world and vast majority of this burden occurs in developing countries especially in Nepal. The study was aimed for determining the various risk factors of anaemia in group of pregnant women of eastern region located in Nepal. To assess prevalence of anaemia and to identify the association between the demographic variables of pregnant women of eastern region. Thus there is necessity for investigate the prevalence of anaemia for pregnant women. This was a follow-up study design was for the study in Obstetrics and Gynaecology department, Birat Medical College & Teaching Hospital, Biratnagar conducted from Oct. 2014 to Jan. 2016.A total of 545 pregnant women were enrolled in this study. Venous blood was obtained for determination of haemoglobin and questionnaire was designed to collect age of marriage, age of first child birth and socioeconomic status. Women were followed up at delivery. Haemoglobin levels of 10-10.9 g/dl, 7.0-9.9 g/dl and <7 g/dl were considered as mild, moderate severe anaemia respectively. The collected data were analysed using SPSS 2, programme. Chi-square test and p-value was used. A total of 545 pregnant women were included in this study. Their mean age was 25.93±4.60. The overall prevalence of anaemia was 40.7% (N=222). The mild, moderate and severe anaemia were at rates of 55.0% (N=122),39.2% (N=87) and 5.9% (N=13) respectively. Women aged 20-24 years were found more anemic with prevalence by severity of 42.8% (N=95). The mean age of marriage and first child birth were 21.92±3.02 and 23.47±2.96 respectively. Majority of pregnant women were at high school level with nuclear family and monthly income NRs<5000 were 35.0% (N=191). Anaemia is significant risk factor for maternal mortality in Nepal. Prevalence of anaemia during pregnancy was 40.7% and this rate is higher to those indicated in others developing countries. In our study population Women with pregnancy had a higher risk of anaemia at the age group 20-24 years by severity of 42.8%. The study revealed that anaemia present at considerable levels in eastern Nepal.